Dimensionering av klimatsystem vid Hietalas växthus i Övertorneå. - Nordell, Bo (Luleå tekniska universitet, Arkitektur och vatten, 1987)
The Hietala Greenhouse is used for cucumber production at the Polar Circle in Sweden. The problem was that the greenhouse temperature varied too much over the day (50C) and that the humidity fell out because of low night temperatures. The suggested system solves this problem by extraction hot humid air under the ceiling during daytime, and pumping this air into drainage pipe in the ground under the cucumbers. Ten the ground cools the air and the humidity falls out in the pipe. Part of the air, and the water, flow through the holes of the drainage pipe into the surrounding soil. When the air leaves the pipe it has been cooled from initial 55C down to about 25. This system was later realized and used for about 20 years before the greenhouse was abandoned. Godkänd; 1987; 20140402 (bon)